Contraindications to intravenous thrombolysis in prehospital triage of thrombectomy candidates. (1st August 2020) - Rodríguez‐Pardo, J.; Secades‐García, S.; Riera‐López, N.; Alonso de Leciñana, M.; Real‐Martínez, V.; Carneado‐Ruiz, J.; Díaz‐Guzmán, J.; Díez‐Tejedor, E.; Egido‐Herrero, J.; Gil‐Núñez, A.; Matute‐Lozano, M. C.; Trillo, S.; et al.
Abstract : Background and purpose: The existence of contraindications to intravenous thrombolysis (IVT) is considered a criterion for direct transfer of patients with suspected acute stroke to thrombectomy‐capable centers in the prehospital setting. Our aim was to assess the utility of this criterion in a setting where routing protocols are defined by the Madrid – Direct Referral to Endovascular Center (M‐DIRECT) prehospital scale. Methods: This was a post hoc analysis of the M‐DIRECT study. Reported contraindications to IVT were retrospectively collected from emergency medical services reports and categorized into late window, anticoagulant treatment and other contraindications. Final diagnosis and treatment rates were compared between patients with and without reported IVT contraindications and according to anticoagulant treatment or late window categories. Results: The M‐DIRECT study included 541 patients. Reported IVT contraindications were present in 227 (42.0%) patients. Regarding final diagnosis no significant differences were found between patients with or without reported IVT contraindications: ischaemic stroke (any) 65.6% vs. 62.1%, ischaemic stroke with large vessel occlusion (LVO) 32.2% vs. 28.3%, hemorrhagic stroke 15.4% vs. 15.6%, stroke mimic 18.9% vs. 22.3% respectively. Amongst patients with LVO, endovascular thrombectomy (EVT) was performed less often in the presence of IVT contraindications (56.2% vs. 74.2%). M‐DIRECT‐positive patients had higher rates of LVO and EVT compared with M‐DIRECT‐negative patients independent of reported IVT contraindications. Conclusions: Reported IVT contraindications alone do not increase EVT likelihood and should not be considered to determine routing in urban stroke networks.